The Optimal Exploitation of Renewable Resource Stocks: Problems of Irreversible Investment - Clark, Colin W.; Clarke, Frank H.; Munro, Gordon R. (Econometrica, 1979)
[This paper studies the effects of irreversibility of capital investment upon optimal exploitation policies for renewable resource stocks. It is demonstrated that although the long-term optimal sustained yield is not affected by the assumption of irreversibility (except in extreme cases), the short-term dynamic behavior of an optimal policy may depend significantly upon the assumption. It is suggested that the results may have profound implications for problems of rehabilitation of overexploited fisheries and other renewable resource stocks.]